Peran Strategi Pemasaran Digital Dalam Meningkatkan Minat Beli Dan Loyalitas Pengguna Aplikasi Tokopedia (Studi Pada Mahasiswa Politeknik Negeri Banjarmasin) - Sari Heppy Maharani; Tarman Effendi (BIMA: Jurnal Bisnis dan Manajemen, 2023)
This study aims to determine the effect of Tokopedia's digital marketing strategy on buying interest and consumer loyalty. Quantitative research methods were used in this study. Questionnaires with a Likert scale were distributed to 40 students of Banjarmasin State Polytechnic using the Tokopedia application. The sampling method used was convenience sampling, namely by distributing questionnaires to students who were on the Banjarmasin State Polytechnic campus. The data obtained is then processed using path analysis. The findings of this study indicate that the variabels of product diversity and promotion through sosial media affect online buying interest. In addition, it was also found that purchase intention significantly influences loyalty despite its small value.